2009
DOI: 10.1007/s12011-009-8399-5
|View full text |Cite
|
Sign up to set email alerts
|

Relative and Combined Effects of Chronic Alcohol Consumption and HCV Infection on Serum Zinc, Copper, and Selenium

Abstract: In alcoholic hepatitis, Kupffer cells are activated by intestinal gram-bacteria, leading to cytokine production and free radicals release, which, enhancing cytokine secretion, create a positive feedback loop which contributes to liver inflammation. Free radicals also damage the liver in chronic hepatitis C virus (HCV) infection, a condition frequently associated to alcohol consumption. In both situations, activity of antioxidant enzymes and of its cofactors zinc (Zn), selenium (Se), and copper (Cu) is importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In addition to alcohol consumption, the relationship between serum copper levels (as well as zinc and selenium) and HCV infection was investigated in a paper by Gonzalez-Reimers et al (2009) [60]. In this research paper, no interaction was found between serum copper levels and alcohol consumption, but a direct relationship was confirmed between serum Cu levels and HCV infection.…”
Section: Copper Levels In Alcoholismmentioning
confidence: 93%
“…In addition to alcohol consumption, the relationship between serum copper levels (as well as zinc and selenium) and HCV infection was investigated in a paper by Gonzalez-Reimers et al (2009) [60]. In this research paper, no interaction was found between serum copper levels and alcohol consumption, but a direct relationship was confirmed between serum Cu levels and HCV infection.…”
Section: Copper Levels In Alcoholismmentioning
confidence: 93%
“…Included studies were conducted in Asia (19 studies), Africa (1 study), Europe (25 studies), and the USA (5 studies). On the other hand, according to the types of liver diseases, 7 were on fatty liver diseases [ 16 , 17 , 30 , 31 , 32 , 33 , 34 ], 22 on hepatitis [ 13 , 19 , 33 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ], 32 on liver cirrhosis [ 13 , 30 , 31 , 33 , 35 , 36 , 37 , 38 , 39 , 41 , 42 , 44 , 48 , 50 , 52 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ,…”
Section: Resultsmentioning
confidence: 99%
“…Included studies were conducted in Asia (19 studies), Africa (1 study), Europe (25 studies), and the USA (5 studies). On the other hand, according to the types of liver diseases, 7 were on fatty liver diseases [16,17,[30][31][32][33][34], 22 on hepatitis [13,19,33,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53], 32 on liver cirrhosis [13,30,31,33,[35][36][37][38][39]41,42,44,48,50,52,[54][55][56][57][58][59]…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In addition, GPx activity is reduced along with selenium levels in CHC ( r = 0.374, p = 0.148), providing a possible mechanism by which CHC stimulates oxidative stress due to selenium deficiency [87]. While others have found no significant reduction in serum selenium in CHC patients [88], alcohol intake was a major confounding variable as it affects selenium levels [89].…”
Section: Seleniummentioning
confidence: 99%